Biotechnology in Cuba through the glass of the CIGB scientific output: a bibliometric approach - Galbán RodrÃguez, Ernesto; Ramos Gómez, Yassel; Vázquez Castillo, Mariela; Arencibia Jorge, Ricardo (Revista Cubana de Información en Ciencias de la Salud, 2024)
Biotechnology has a strategic weight in the Cuban scientific output. In this context, the Center for Genetic Engineering and Biotechnology (CIGB) plays a fundamental role as the most productive scientific institute of the main Caribbean Island. In this work, the scientific production of this institution was assessed for the first time with an exhaustive bibliometric approach. A full bibliographic record was established, covering the period 1981-2022. Documentary analysis was applied, retrieving its editorial production, records in nine bibliographic databases and author profile pages at ResearchGate and ORCID. Foundational publishing milestones were addressed. Publishing dynamics alone and together with patent applications were studied, as well as its main properties and evolution. A total of 3667 institutional documents were studied, 66.6% of them indexed in mainstream databases, with an H index of 74. Institutional authors led the 69.45% of papers. The study confirmed CIGB as the top Cuban research institution attending to the number of works covered by Web of Science Core Collection and Scopus, only preceded by major universities. This center contributes 3.64-4.63% of national output in mainstream databases, 4.54-7.21% of cited documents and 6.09-8.10% of citations received by the Cuban output. After a continuous growing period, the output remained steady since the foundation of the Cuban Biotechnological and Pharmaceutical Industry (BioCubaFarma) in 2012, particularly in foreign indexed journals, and it was boosted since 2020 by the covid-19/sars-cov-2 pandemics. An updated ranking of Cuban institutions was also included, with CIGB in the top five ranking position.